Rare earth aluminum alloy conductor material and preparation method thereof
By introducing trace elements and specific heat treatment processes into aluminum alloys, the problem of the conductivity of aluminum alloy conductor materials decreasing when improving mechanical strength is solved, and the high mechanical strength and high conductivity are achieved, and the efficiency of power transmission is improved.
Patent Information
- Application Number
- CN202411817598.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-18
AI Technical Summary
While the existing aluminum alloy conductor materials increase mechanical strength, the conductivity has significantly decreased, resulting in an increase in energy loss during power transmission, making it difficult to meet the modern society's demand for efficient power transmission.
By introducing trace amounts of magnesium, silicon, boron and rare earth elements into the aluminum alloy, the rare earth aluminum alloy conductor material is formed, and a specific heat treatment process is adopted, including solution treatment, annealing treatment and aging treatment to improve the mechanical properties and electrical conductivity of the alloy.
It achieves the mechanical strength of aluminum alloy conductor materials while maintaining or approaching the conductivity of pure aluminum, reducing energy losses during power transmission, and improving energy utilization efficiency.
Smart Images

Figure CN119843117A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal alloys, and in particular relates to a rare earth aluminum alloy conductor material and a preparation method thereof. Background Art
[0002] Aluminum and aluminum alloys have been widely used in the field of power transmission and distribution due to their advantages such as light weight, corrosion resistance and good processing performance. The electrical conductivity of pure aluminum is as high as about 65% IACS (International Annealed Copper Standard), which has significant advantages in electrical conductivity. However, the mechanical strength of pure aluminum is low, which limits its application in power lines with high strength requirements.
[0003] In order to improve the mechanical strength of aluminum conductors, alloying elements such as magnesium, silicon, copper, etc. are usually added to aluminum to form aluminum alloys. Although the addition of these alloying elements enhances the mechanical properties, it often leads to a significant decrease in electrical conductivity. For example, the conductivity of common aluminum-magnesium-silicon alloys is usually only about 52% IACS. This reduction in electrical conductivity will increase energy loss during power transmission, which is not conducive to improving the transmission efficiency of the power grid. With the continuous growth of modern society's demand for electric energy, reducing transmission losses and improving energy utilization efficiency have become important issues in the power industry. Therefore, there is an urgent need for an aluminum alloy conductor material that has high mechanical strength without sacrificing electrical conductivity. While maintaining or approaching the electrical conductivity of pure aluminum, improving the mechanical strength of the conductor will help to achieve a lightweight, high-efficiency power transmission system to meet the needs of future power grid development.
[0004] Through appropriate heat treatment (such as aging treatment), the solute atoms in the supersaturated solid solution are precipitated to form second phase particles. After these particles are precipitated from the matrix, the content of solute atoms in the matrix is reduced and the lattice distortion is reduced; by adjusting the heat treatment parameters, the precipitated phase will also grow and the interface area will be reduced; heat treatment can also reduce the dislocation density, release the internal stress accumulated during the processing, reduce the lattice distortion, and reduce the hindrance to electron migration. The influence of heat treatment on the conductivity of aluminum alloy is multifaceted, and a balance needs to be struck between improving mechanical properties and maintaining high conductivity. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a rare earth aluminum alloy conductor material.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a rare earth aluminum alloy conductor material, characterized in that: the rare earth aluminum alloy conductor material comprises magnesium, silicon, boron and a rare earth element, the rare earth element comprises one of lanthanum, cerium, yttrium and erbium, and the rest is aluminum;
[0009] Wherein, in terms of mass fraction, the mass fraction of magnesium is 0.2% to 0.8%, the mass fraction of silicon is 0.1% to 0.5%, the mass fraction of boron is 0.01% to 0.15%, the mass fraction of rare earth elements is 0.1% to 0.15%, and the rest is aluminum.
[0010] As a preferred solution of the rare earth aluminum alloy conductor material of the present invention, the mass fraction of magnesium is 0.6%, the mass fraction of silicon is 0.5%, and the mass fraction of boron is 0.12%.
[0011] As a preferred solution of the rare earth aluminum alloy conductor material of the present invention, the conductivity of the rare earth aluminum alloy conductor material is 60% IACS.
[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a rare earth aluminum alloy conductor material.
[0013] To solve the above technical problems, the present invention provides the following technical solution: the rare earth aluminum alloy conductor material is obtained by batching, smelting, slag removal, degassing, heat preservation, casting, solution treatment, annealing and aging according to the mass percentage.
[0014] As a preferred embodiment of the preparation method of the present invention, the smelting temperature is 600°C to 800°C.
[0015] As a preferred embodiment of the preparation method of the present invention, the heat preservation time is 10 to 60 minutes.
[0016] As a preferred embodiment of the preparation method of the present invention, the solution treatment temperature is 510° C. and the time is 1.5 h.
[0017] As a preferred embodiment of the preparation method of the present invention, the annealing treatment temperature is 300° C. to 530° C., and the time is 8 to 12 hours.
[0018] As a preferred embodiment of the preparation method of the present invention, the aging treatment temperature is 190° C. and the time is 8 hours.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a rare earth aluminum alloy conductor material for use in the field of electric energy transmission.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention introduces trace elements as microalloying elements into aluminum alloys. The atomic radius of these microalloying elements is usually much larger than that of aluminum, and the solid solubility in the aluminum matrix is very low, which avoids lattice distortion and electron scattering caused by a large number of solute atoms and reduces the negative impact on conductivity; and their electronic orbits (such as 4f and 5d orbits) are complex and easy to form stable intermetallic compounds or second phase particles. Due to their size and distribution, these second phase particles can effectively hinder dislocation movement and improve the strength of the alloy, but will not significantly affect the migration of electrons in the matrix; at the same time, the second phase particles formed by the microalloying elements usually have a high melting point and high stability, and can maintain their morphology and distribution during heat treatment and use. These particles can refine the grains and strengthen the alloy, but due to the interface properties between them and the matrix, the effect on electron scattering is very limited; microalloying elements can also be concentrated at the grain boundaries, reduce grain boundary energy, inhibit grain growth, and stabilize the microstructure of the alloy. At the same time, these elements help to reduce the impurity and gas content in the melt, reduce defect density, and further improve conductivity. By precisely controlling the amount of microalloying elements added, they are mainly present in the aluminum alloy as an independent second phase, which minimizes the solid solution of solute atoms in the matrix, reduces lattice distortion and electron scattering. This design concept greatly improves the mechanical properties of the alloy while maintaining or approaching the electrical conductivity of pure aluminum, achieving both high strength and high electrical conductivity.
[0022] (2) The different heat treatment methods of the present invention reduce the generation of internal stress and cracks, and obtain a dense casting structure. During the casting process, the rapid cooling of the molten metal will lead to the accumulation of thermal stress and increase the risk of cracks. Preheating the mold can reduce the temperature difference and reduce the cooling rate, thereby reducing the internal stress and preventing the casting from generating thermal cracks and stress cracks. Long-term heat preservation at 300°C will cause some alloy elements (such as Mg and Si) to slowly precipitate and form dispersed small particle precipitation phases. These precipitation phases can strengthen the alloy, but because they are small and dispersed, they may increase the scattering of electrons. Relatively low temperatures make the grain boundary movement and recrystallization not obvious. The fine precipitation phase may hinder the movement of dislocations, but it is beneficial to maintain a relatively stable electron migration channel. At a higher temperature of 400°C, the morphology and quantity of the precipitation phase will change, and the small particle precipitation phase may grow and reduce the interface area. This will reduce the scattering of electrons at the interface, which is beneficial to conductivity. Higher temperatures can release some internal stress, reduce lattice distortion and dislocation density, thereby reducing electron scattering and improving conductivity. The short-time heat treatment at 530°C belongs to the solution treatment, and most of the alloy elements will be redissolved in the matrix to form a supersaturated solid solution. As the precipitated phase is redissolved, the crystal structure tends to be uniform, which helps to reduce electron scattering. In the subsequent 8-hour heat preservation process at 270°C, the solute atoms are re-precipitated to form dispersed second phase particles. The distribution of the precipitated phase is relatively uniform, but because the temperature is lower than 300°C, its size is small and the number is large, which may increase some electron scattering. Such a heat treatment scheme is more suitable for aluminum alloy conductors that need to take into account both high conductivity and mechanical properties. The solution treatment temperature of the present invention is 510°C and the time is 1.5h; by dissolving the Mg2Si strengthening phase, the solute elements in the alloy are evenly distributed in the aluminum matrix. The annealing treatment conditions of the present invention are 300°C / 12h or 400°C / 12h or 530°C / 2h+270°C / 8h; the temperature of 300°C is relatively low, which is suitable for eliminating the internal stress that may be generated in aluminum alloys during casting or cold working. This temperature will not significantly change the strengthening phase or grain size, so the strength of the alloy will not decrease significantly, and the plasticity will be moderately improved. The temperature of 400°C can promote the recovery and recrystallization of internal dislocations, improve the plasticity of the alloy, and reduce internal stress. The high temperature of 530°C is sufficient to dissolve most of the Mg2Si precipitates in the alloy, and the heating time of 2 hours can ensure that most of the precipitates are dissolved without causing excessive coarsening of the grains. At a temperature of 270°C, the dissolved elements in the alloy (such as magnesium and silicon) will begin to re-precipitate to form fine and evenly distributed Mg2Si particles. The refinement of the precipitates helps to restore the strength of the alloy. The aging treatment temperature of the present invention is 190°C and the time is 8h; the temperature of 190°C is relatively moderate, which can promote the precipitation of Mg2Si in the matrix and form fine and uniform precipitates. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 This is a physical picture of the rare earth aluminum alloy conductor material of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0029] Table 1
[0030] name Commercial channels Part Number High purity aluminum particles Northeast Nonferrous Metals 113007 Aluminum Silicon Alloy Northeast Nonferrous Metals 313141 Aluminum-magnesium alloy Northeast Nonferrous Metals 313121 Aluminum Boron Alloy Northeast Nonferrous Metals 313051 Aluminum Lanthanum Alloy Northeast Nonferrous Metals 313398 Aluminum Cerium Alloy Northeast Nonferrous Metals 313399 Aluminum Erbium Alloy Northeast Nonferrous Metals 313681
[0031] Example 1
[0032] The present invention provides a method for preparing a rare earth aluminum alloy conductor material:
[0033] In terms of mass percentage, the alloy comprises the following components: 0.6% Mg, 0.5% Si, 0.12% La, and the balance Al.
[0034] Pure aluminum was heated to 720°C for melting, and then subjected to slag removal and degassing treatments and kept warm for 20 minutes. Al-Mg, Al-Si, and Al-La alloys were added and stirred for 5 minutes. After slag removal and degassing treatments, the mixture was kept warm for 20 minutes. The mixture was cast into a mold (preheated to 200°C), and after cooling, it was kept at 510°C for 1.5 hours to obtain an Al-0.6Mg-0.5Si-0.12La ingot.
[0035] Example 2
[0036] The difference from Example 1 is that, in terms of mass percentage, it includes the following components: 0.6% Mg, 0.5% Si, 0.12% B, 0.1% La, and the balance is Al. Pure aluminum is heated to 720°C for melting, slag removal and degassing are performed, and then the temperature is kept for 20 minutes. Al-Mg, Al-Si, Al-La, and Al-B alloys are added and stirred for 5 minutes, slag removal and degassing are performed, and then the temperature is kept for 20 minutes, and then cast into a mold (preheated at 200°C), and then cooled and kept at 510°C for 1.5 hours to obtain an Al-0.6Mg-0.5Si-0.12B-0.12La ingot.
[0037] Example 3
[0038] The difference from Example 1 is that, in terms of mass percentage, it includes the following components: 0.6% Mg, 0.5% Si, 0.12% B, 0.12% La, and the balance is Al.
[0039] Example 4
[0040] The difference from Example 1 is that, in terms of mass percentage, it includes the following components: 0.6% Mg, 0.5% Si, 0.12% B, 0.1% Ce, and the balance is Al.
[0041] Example 5
[0042] The difference from Example 1 is that, in terms of mass percentage, it includes the following components: 0.6% Mg, 0.5% Si, 0.12% B, 0.1% Er, and the balance is Al.
[0043] Comparative Example 1
[0044] The difference from Example 1 is that, in terms of mass percentage, it includes the following components: 0.6% Mg, 0.5% Si, and the balance is Al.
[0045] Example 6
[0046] The conductivity of the ingots obtained in Examples 1 to 5 and the comparative example was tested:
[0047] Use a metal eddy current conductivity meter: PZ 60A, calibrate after powering on, place the probe on the high standard block, press the OK key after the value is displayed, place the probe in the air and press the OK key, then switch to the low standard block and repeat the operation. Then press the measurement key, select the area with a flat surface and no obvious oxide layer or other contaminants as the test sample, select at least 5 points on the surface and cross section of Examples 1-3 and Comparative Example 1 for measurement, record the data, and take the average value.
[0048] Table 2
[0049] As-cast electrical conductivity (% IACS) Comparative Example 1 Al-0.6Mg-0.5Si 50.5 Example 1 Al-0.6Mg-0.5Si-0.12La 50.2 Example 2 Al-0.6Mg-0.5Si-0.12B-0.1La 51.3 Example 3 Al-0.6Mg-0.5Si-0.12La-0.12B 50.7 Example 4 Al-0.6Mg-0.5Si-0.12B-0.1Ce 49.5 Example 5 Al-0.6Mg-0.5Si-0.1Er-0.12B 50.7
[0050] Comparative Example 2
[0051] The difference from Comparative Example 1 is that the ratios of Mg:Si are 1.4, 1.6 and 1.8 respectively. The conductivity test results of the obtained ingots are as follows:
[0052] Table 3
[0053] Mg:Si ratio Si content (%) Electrical conductivity (%IACS) 1.2 0.5 50.5 1.4 0.5 49.3 1.6 0.5 48.1 1.8 0.5 46.8
[0054] Comparative Example 3
[0055] The difference from Example 2 is that the content of rare earth element LA is 0.12% and 0.15%. The test results of conductivity of the obtained ingots are as follows:
[0056] Table 4
[0057] Rare Earth Elements content(%) Electrical conductivity (%IACS) LA 0.1 51.3 LA 0.12 50.7 LA 0.15 50.0
[0058] Comparative Example 4
[0059] The difference from Example 4 is that the content of rare earth element Ce is 0.12% and 0.15%. The test results of conductivity of the obtained ingots are as follows:
[0060] Table 5
[0061] Rare Earth Elements content(%) Electrical conductivity (%IACS) Ce 0.1 49.5 Ce 0.12 49.3 Ce 0.15 48.8
[0062] Comparative Example 5
[0063] The difference from Example 5 is that the conductivity test results of the ingots obtained when the content of the rare earth element Er is 0.12% and 0.15% are as follows:
[0064] Table 6
[0065] Rare Earth Elements content(%) Electrical conductivity (%IACS) Er 0.1 50.7 Er 0.12 50.5 Er 0.15 49.9
[0066] Example 7
[0067] The ingot obtained in Example 1 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0068] Example 8
[0069] The ingot obtained in Example 2 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, and 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0070] Example 9
[0071] The ingot obtained in Example 3 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0072] Example 10
[0073] The ingot obtained in Example 4 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, and 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0074] Embodiment 11
[0075] The ingot obtained in Example 5 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0076] Comparative Example 6
[0077] The ingot obtained in Comparative Example 1 was subjected to heat treatment at 300°C / 12h, 400°C / 12h, and 530°C / 2h+270°C / 8h, respectively, and then subjected to aging treatment at 190°C / 8h to obtain an aluminum alloy conductor material.
[0078] The electrical conductivity of the materials obtained in Examples 7 to 11 and Comparative Example 6 was tested and the results are as follows.
[0079] Table 7
[0080]
[0081] Figure 1 The results show that different rare earths were added to the aluminum alloy conductor materials of the present invention, and the conductivity of Examples 1 to 5 was greatly improved compared with the cast state. Among them, the aluminum alloy of Example 9 had a conductivity of 60% IACS after being kept at 400°C for 12 hours, which was the best performance.
[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A rare earth aluminum alloy conductor material, characterized in that: The rare earth aluminum alloy conductor material includes magnesium, silicon, boron and rare earth elements, wherein the rare earth element includes one of lanthanum, cerium, yttrium and erbium, and the rest is aluminum; Wherein, in terms of mass fraction, the mass fraction of magnesium is 0.2% to 0.8%, the mass fraction of silicon is 0.1% to 0.5%, the mass fraction of boron is 0.01% to 0.15%, the mass fraction of rare earth elements is 0.1% to 0.15%, and the rest is aluminum.
2. The rare earth aluminum alloy conductor material according to claim 1, characterized in that: The mass fraction of magnesium is 0.6%, the mass fraction of silicon is 0.5%, and the mass fraction of boron is 0.12%.
3. The rare earth aluminum alloy conductor material according to claim 1 or 2, characterized in that: The electrical conductivity of the rare earth aluminum alloy conductor material is 60% IACS.
4. The method for preparing the rare earth aluminum alloy conductor material according to claims 1 to 3, characterized in that: include, The materials are batched, smelted, slag removed, degassed, heat-insulated, cast, and then solution treated according to the mass percentage of any one of claims 1 to 2. 、 The rare earth aluminum alloy conductor material is obtained after annealing and aging treatment.
5. The preparation method according to claim 4, characterized in that: The smelting temperature is 600°C to 800°C.
6. The preparation method according to claim 4, characterized in that: The insulation time is 10 to 60 minutes.
7. The preparation method according to claim 4, characterized in that: The solution treatment temperature is 510° C. and the time is 1.5 h.
8. The preparation method according to claim 4, characterized in that: The annealing treatment temperature is 300° C. to 530° C., and the time is 8 to 12 hours.
9. The preparation method according to claim 8, characterized in that: The aging treatment temperature is 190° C. and the time is 8 hours.
10. Application of the rare earth aluminum alloy conductor material as claimed in claim 9 in the field of electric energy transmission.
Citation Information
Cited By
High-conductivity and high-strength aluminum alloy material as well as heat treatment method, preparation method and application thereof
CN120866751A